Between financial, environmental and health concerns: the role of risk perceptions in modeling efuel acceptance - Arning, Katrin; Offermann, Julia; Engelmann, Linda; Gimpel, Regina; Ziefle, Martina (Frontiers in Energy Research, 2025)
The transition towards sustainable and defossilized mobility systems relies on public perception and acceptance of innovations like efuels. Understanding the role of risk perceptions and their different dimensions in shaping public acceptance is therefore critical for facilitating the introduction of efuels into mobility systems. A quantitative survey was conducted among a representative sample of 517 German participants to assess their risk perceptions and acceptance of efuels. A Structural Equation Modeling (SEM) approach was employed to analyze the relationships between cognitive, affective, and domain-specific risk perceptions (health, environmental, and financial) and public acceptance of efuels. The analysis revealed low levels of both cognitive and affective risk perceptions as well as positive acceptance levels for efuels. Financial risk perception was more pronounced than health or environmental risk perceptions. Affective and cognitive risk perceptions were found to negatively impact acceptance, with cognitive risk perception showing a stronger influence. Environmental risk perception was negatively associated with acceptance, while health and financial risks showed no significant association. The findings suggest that while efuels are generally accepted, financial and environmental concerns might hinder widespread adoption. Addressing these concerns through targeted communication strategies that combine cognitive (economic, environmental) and affective (health) dimensions is essential for a socially accepted design of sustainable mobility systems.